2020
DOI: 10.11648/j.ajls.20200804.16
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Silver Nano Particles Synthesized from <i>Ficus sycomorus</i> <i>Linn</i> Against Multidrug Resistant <i>Shigella species</i> Isolated from Clinical Specimens

Abstract: Ficus sycomorus Plant was known traditionally for its medicinal properties, Shigella species as a bacterial was also known for their resistance to orthodox medicine. Hence the synthesis of silver nanoparticles from Ficus sycomorus. This study was carried out to investigate the anti-shigellosis potential of silver nanoparticles synthesized from Ficus sycomorus Linn stem bark aqueous extract against Multi-drug Resistant (MDR) Shigella species isolated from clinical specimen collected from patients attending Yobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The results showed that the spectra of the methanolic extract of pumpkin peels revealed the presence of different functional groups, as well as FTIR analysis, such as the phenolic group, the C-H stretch, the N-H stretch, the C-C stretch, in addition to the C-N stretch. The peaks that fall within the range of 4000 to 3200 cm -1 , as well as the range of 2935.66 cm -1 , indicate O-H stretching and C-H stretching, respectively [29], which confirms the presence of carboxylic acids, primary amines, and alkanes [33]. As for the absorption peak 1595.13 cm -1 is the (N-H) stretch that confirms carbonyl groups [34], the peak of 1406.11 cm -1 indicates the C-C stretch that confirms the presence of aromatic compounds and the symmetrical N-O stretch that indicates the presence of nitro compounds [35], showing the appearance The peaks at 1105.21 and 1076.28 cm -1 are due to (OH) and (C-H, C-O), respectively [36].…”
Section: Fourier Transformation Infrared Spectroscopy (Ftir)mentioning
confidence: 86%
“…The results showed that the spectra of the methanolic extract of pumpkin peels revealed the presence of different functional groups, as well as FTIR analysis, such as the phenolic group, the C-H stretch, the N-H stretch, the C-C stretch, in addition to the C-N stretch. The peaks that fall within the range of 4000 to 3200 cm -1 , as well as the range of 2935.66 cm -1 , indicate O-H stretching and C-H stretching, respectively [29], which confirms the presence of carboxylic acids, primary amines, and alkanes [33]. As for the absorption peak 1595.13 cm -1 is the (N-H) stretch that confirms carbonyl groups [34], the peak of 1406.11 cm -1 indicates the C-C stretch that confirms the presence of aromatic compounds and the symmetrical N-O stretch that indicates the presence of nitro compounds [35], showing the appearance The peaks at 1105.21 and 1076.28 cm -1 are due to (OH) and (C-H, C-O), respectively [36].…”
Section: Fourier Transformation Infrared Spectroscopy (Ftir)mentioning
confidence: 86%
“…Carbohydrate [mannitol, maltose, dulcitol, sucrose and glucose] was inoculated with drop of the nutrient broth suspension of the test isolate and loosely capped and incubated at 37ºC overnight. They were observed for change in colour from amber to red and for gas production (in the medium filled inverted Durham tube)" [14].…”
Section: Sugar Fermentation Testsmentioning
confidence: 99%
“…After the preparation of the nanoparticles, the suspension of nanoparticles in distilled water was used for SEM analysis by fabricating a drop of suspension onto a clean carbon-coated corer grid and allowing water to completely evaporate. The dried sample was then mounted with the aid of a sample holder 15,16 . An Enlarged SEM image was observed 5 .…”
Section: Semmentioning
confidence: 99%
“…3(b). The colour change to light brown has been attributed to plasmons resonance formation on the surface of the molecules and oscillation of metal nanoparticles conduction electrons 16 .…”
Section: Synthesized Particlesmentioning
confidence: 99%